2020
DOI: 10.1186/s13063-020-04703-6
|View full text |Cite
|
Sign up to set email alerts
|

Motivational nondirective resonance breathing versus transcutaneous vagus nerve stimulation in the treatment of fibromyalgia: study protocol for a randomized controlled trial

Abstract: Background Chronic widespread pain (CWP), including fibromyalgia (FM), affects one in every ten adults and is one of the leading causes of sick leave and emotional distress. Due to an unclear etiology and a complex pathophysiology, FM is a condition with few, if any, effective and safe treatments. However, current research within the field of vagal nerve innervation suggests psychophysiological and electrical means by which FM may be treated. This study will investigate the efficacy of two diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 129 publications
(147 reference statements)
0
12
0
Order By: Relevance
“…Study design and clinical trial protocol was peer-reviewed and published [see trial protocol ( 31 )]. FM participants were consecutively recruited from, (1) the Department of Pain Management and Research at Oslo University Hospital, in Oslo, Norway; (2) the surrounding Oslo community; and (3) from the south-east region of Norway.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study design and clinical trial protocol was peer-reviewed and published [see trial protocol ( 31 )]. FM participants were consecutively recruited from, (1) the Department of Pain Management and Research at Oslo University Hospital, in Oslo, Norway; (2) the surrounding Oslo community; and (3) from the south-east region of Norway.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were 18–65 years of age with severe FM that persisted at least 3 months or more with an average self-report NRS pain intensity of 6-10. A full list of study exclusion criteria can be found in trial protocol ( 31 ). Participants provided both oral and written informed consent for participation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…rMSSD is a reliable HRV measure under ultrashort recording windows (#1 minute) 16 and is not confounded by respiratory effects. 34,50…”
Section: Heart Rate Variabilitymentioning
confidence: 99%